Psychological aspect of professional selection in the service in law enforcement bodies - Prokopiv, Bohdan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
At the current stage of development of Ukrainian society, the problem of ensuring the sound functioning of state authorities and law enforcement agencies is relevant. One of such formations is the bodies of internal affairs (hereinafter - ATS), which are responsible and difficult task - protection of society from criminal encroachments. Successful implementation of this difficult task depends on the willingness and ability of each employee to perform their professional duties at an appropriate level.It is worth noting that the ATS has a fairly rapid staff turnover due to high requirements for employees of this kind of activity. The selection of personnel for service in the ATS is a complex task that requires the involvement of a large number of specialists from different sectors for the full and accurate selection of personnel